Xanthogranulomatous appendicitis in interval appendectomy specimens of children - Yusuf Hakan Çavuşoğlu; Burak Ardıçlı; Sema Apaydın; Çağatay Evrim Afşarlar; Engin Yılmaz (Elsevier, 2016)
Xanthogranulomatous inflammation is common in interval appendectomy specimens in adults, but it is unusual in children. Histopathologic specimens of interval appendectomy, within an 8-year period, were reevaluated to assess the true incidence. A computer search of the hospital database of all appendectomies was performed between January 2008 and June 2015 to identify all interval appendectomy cases. A total of 2694 patients underwent appendectomies. Of these, 13 were interval appendectomies. After pathologic evaluation, 2 (15.4%) of the specimens were reported as xanthogranulomatous appendicitis (XA). Histopathologic examination of these interval appendectomy specimens, granulomas (59%), xanthogranulomatous inflammation (36%) and Crohn-like changes (50%) were common in adults. However, XA is a particularly rare clinical entity among children. Two cases of XA were reported in children in the English literature. One was a 12-year old boy that underwent interval appendectomy 6 weeks after an episode of acute appendicitis. The other was an 11-year old boy with acute (non-interval) appendicitis, but the complete blood count was suggestive of an acute suppurative inflammation. These two cases are the 3rd and 4th cases of XA reported in children in the English literature, and both were managed by interval appendectomy. Thus, XA may be encountered in interval appendectomy specimens and association with IBD has to be ruled out.